Study of pitting corrosion on mild steel and stainless steel by electrochemical noise technique - Hashim, I. H.; Hamzah, K. (Faculty of Science, 2009)
Pitting corrosion can be analyzed using electrochemical noise technique. Both mild steel and stainless steel samples were immersed in NaCl solution. Two different concentrations of NaCl solution were used; 1.0 M and 0.1 M. CaOH solutions was added to the electrochemical cell which contains mild steel sample to create a passivating layer on the sample. The chloride ions attacked the layers and form pitting corrosion. The cell was connected to a digital multimeter and was placed in a Faraday Cage. The data was processed and transferred to a computer for storage